Onto Center Stage : the Biblical Woman - Reguer, Sara (Academic Studies Press, 2022)
The Biblical narrative is usually very terse and cryptic. Over the millennia, Jewish scholars often painted a patriarchal picture with women 'in their place'. This book puts these women--some are role models--into the context of an ancient society, bringing them imaginatively from the sidelines onto center stage.